Revisiting Banks' Performance After the Digitalization Acceleration: The Case of Conventional Banking Industry in Indonesia - Rachmawati, Puput Decpa; Pimada, Laila Masruro (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
Otoritas Jasa Keuangan (OJK) facilitates digital banking acceleration by establishing regulations related to digital banking. After its implementation, banking performance in general has increased, but some banks experienced discrepancies. This study aims to analyze the comparison of banks’ fund composition, operational efficiency, and economic rentability before and during the acceleration. This research uses the comparative tests by the Wilcoxon Signed Rank Test and Paired Sample T-Test based on the existing data of nine banks listed on the Indonesia Stock Exchange (IDX) main board. The result indicates that there were significant differences in banks’ Current Account Saving Account composition, operational efficiency, and economic rentability variables. In contrast, banks’ Time Deposit composition variables did not experience significant differences before and after digitalization acceleration. This study was conducted based on the data from IDX main board banks that have provided online account opening features and experienced a decline in one of the fund composition, operational efficiency, and economic rentability performance.